Metabotropic glutamate receptors are differentially regulated under elevated intraocular pressure. - Dyka; May; Enz, Ralf (Journal of Neurochemistry, 2004)
Glaucoma is a leading cause of blindness, ultimatively resulting in the apoptotic death of retinal ganglion cells. However, molecular mechanisms involved in ganglion cell death are poorly understood. While the involvement of ionotropic glutamate receptors has been extensively studied, virtually nothing is known about its metabotropic counterparts. Here, we compared the retinal gene expression of metabotropic glutamate receptors (mGluR) in eyes with normal and elevated intraocular pressure (IOP) of DBA/2J mice, a model for secondary angle-closure glaucoma using RT-PCR and immunohistochemistry. Elevated IOP in DBA/2J mice significantly increased retinal gene expression of mGluR1a, mGluR2, mGluR4a, mGluR4b, mGluR6 and mGluR7a when compared to C57BL/6 control animals, while mGluR5a/b and mGluR8a were decreased and no difference was observed for mGluR3 and mGluR8b. Specific antibodies detected an increase of mGluR1a and mGluR5a/b in both synaptic layers and in the ganglion cell layer of the retina under elevated IOP. Because ganglion cell death in DBA/2J mice occurs most likely by apoptotic mechanisms, we demonstrated up-regulation of mGluRs in neurons undergoing apoptosis. In summary, we support the idea that the specific gene regulation of mGluRs is a part of the glaucoma-like pathological process that develops in the eyes of DBA/2J mice.
UnivIS-Import:2017-12-18:Pub.2004.med.IB.profes_1.metabo
Keywords: Apoptosis; Gene expression; Glaucoma; Immunocytochemistry; Retina; RT-PCR